The Role of Organizational Agility and Its Achieving Organizational Effectiveness: A Field Study by Carried Out on the Arab Sudanese Seeds Company (2023) - Abdelbasit, Tilal Khalid (The Arab Journal of Administration, 2024)
The study aimed at identifying organizational agility and its role in achieving organizational effectiveness, a field study by carried out on the Arab Sudanese Seeds Company as case study to achieve the objectives of the study.Descriptive analytical method was used the study population consisted of all employees working in the Arab Sudanese Seeds Company for a sample of (65). The following are the most important results. The most important of which is the availability of organizational agility in a medium degree, amounting to (2.65), while the availability of organizational effectiveness in a low degree, amounting to (2.47). The study concluded that there is a strong positive significant correlation between the dimensions of organizational agility and organizational effectiveness, amounting to (0.815). It recommended raising the level of the practice dimension and It also recommended raising the level of organizational effectiveness to a stronger level, by paying attention to the preferences and needs of customers, while providing modern technologies that allow the company to seize the opportunities available in the external environment, to enjoy a great deal of flexibility.